The ABCs of antiphospholipid syndrome - Ayşe Bahar Keleşoğlu Dinçer,; Doruk Erkan, (Archives of Rheumatology, 2023)
Antiphospholipid syndrome (APS) is a thromboinflammatory syndrome characterized by thrombotic, microvascular, obstetric, or non-thrombotic events in the setting of persistent antiphospholipid antibodies (aPL), namely anticardiolipin antibody (aCL), anti-β2 glycoprotein-I antibody (aβ2GPI), and lupus anticoagulant (LA). The diagnosis of APS requires careful assessment of the aPL profile, the clinical phenotype, and additional risk factors. The standard management of aPL-related thrombosis is anticoagulation, which is not effective for microvascular and non-thrombotic events. In parallel to our improved understanding of aPL-related mechanisms, the role of immunosuppression has been increasingly investigated. In this review, we summarize the basic concepts and future perspectives in APS.